Harnessing digital health interventions to address the heterogeneity of depression: a systematic review - Alsalloum, Ghufran; Dalibalta, Sarah; Hadijat, Yacine (Frontiers in Digital Health, 2025)
BackgroundDepression affects over 229 million people worldwide and ranks among the leading causes of disability and death, particularly in young adults, where suicide is a top contributor to mortality. Standard diagnostic and treatment approaches often overlook the marked clinical and biological heterogeneity of depression, resulting in low first-line remission rates and prolonged trial-and-error care, underscoring an urgent need for precision strategies in mental health practice.ObjectiveThis review explores the recent literature (January 2020–September 2025) on personalized digital health interventions for depression, with an emphasis on how these technologies address heterogeneity in symptomatology, biological underpinnings, and treatment response across diverse patient populations.MethodsThe study followed PRISMA guidelines, searching Scopus, IEEE Xplore, and ClinicalTrials.gov for English-language peer-reviewed articles and trials published and registered between January 2020 and September 2025. Only studies relevant to depression heterogeneity and digital health were included, and studies focusing solely on generic digital health tools without a personalized or adaptive component were excluded. Findings were synthesized narratively.Findings29 publications were reviewed: 20 studies and 9 clinical trial reports, representing over 5,000 participants. Personalized machine-learning models using mobile sensing and ecological momentary assessments improved mood-forecasting accuracy by up to 25%. Randomized trials of just-in-time adaptive interventions (e.g., the Mello app) demonstrated moderate to large effect sizes for reductions in depression (d = 0.50), anxiety (d = 0.61), and repetitive negative thinking (RNT) (d = 0.87). Smart-messaging post-Cognitive Behavioral Therapy yielded sustained well-being improvements over 12 months, while neuromodulation-based digital therapeutics targeting apathy networks in late-life depression showed significant gains in executive function and motivation. Most studies featured small, convenience samples, variable outcome measures, and limited external validation; risk-of-bias concerns included lack of blinding and incomplete handling of missing data. Equity analyses across demographic and clinical subgroups were seldom reported.Conclusionsand Relevance: Digital mental health technologies exhibit substantial promise for delivering personalized interventions that accommodate inter-individual variability in depression. High-quality evidence supports their capacity to enhance prediction, engagement, and clinical outcomes. However, broader implementation requires standardized multidimensional outcome measures, equity-focused algorithm validation, and integration of established clinical phenotypes.